Validation of Annuli Formation in Pectoral Fin Rays from Shovelnose Sturgeon in the Lower Platte River, Nebraska. (9th September 2014) - Rugg, M. L.; Hamel, M. J.; Pegg, M. A.; Hammen, J. J.
Abstract : Fish age is commonly estimated by counting bands on calcified structures. Age estimates are used to calculate information on population dynamics such as growth, mortality, and recruitment. Pectoral fin rays are the most frequently used structure to age sturgeon species, yet little work has been done to validate annuli formation. We collected Shovelnose Sturgeon Scaphirhynchus platorynchus monthly from the lower Platte River, Nebraska, during 2011 and 2012 and removed the leading, left pectoral fin ray from each fish captured. We used marginal increment analysis to assess the validity of annual deposition of growth marks on pectoral fin rays. There were two complete cycles of increasing and decreasing increment values between March and November within each year. Mean marginal increments showed minimal peaks in March, July, and October followed by a decrease in increment length during April, September, and November. However, mean marginal increments were similar between months in both years. These results suggest there is no discernible pattern in growth ring deposition for Shovelnose Sturgeon in the lower Platte River and that their use for age and growth analyses would likely lead to biased estimates. Inaccuracies in age assignment can lead to errors when calculating population dynamic parameters and, ultimately, misguided management decisions. We recommend that alternate methods for estimating the ages of Shovelnose Sturgeon be explored. Received February 25, 2014; accepted July 4, 2014